Monitoring Interfaces Fastethernet on Cisco Catalyst 3750 to Ensure Use of The Security Computer Network In STTA Computing Laboratories - Sudaryanto, Sudaryanto; Nurhayati, Dwi (SENATIK STT Adisutjipto, 2019)
Cisco is a company that concentrates on hardware and software related to computer networks. One of the hardware produced by Cisco is a switch device that can be used for management of a computer network. Many types of switches that have been produced by Cisco, one of which is the Cisco Catalyst 3750. In the configuration and monitoring of the Cisco Catalyst 3750 user / administrator must do management with command line based configuration. This is because Cisco has not facilitated its users with user interface based configurations. So the user is required to know the code syntax to execute a command on the switch. In this study, researchers will discuss about how to create a user interface for monitoring web-based Fastethernet Interfaces on the Cisco Catalist 3750 to ensure the security of using computer networks in STTA computing laboratories that have many interconnected computer devices using e-mail notifications using APIs. The results of the test show that the application can be monitored by the administrator remotely in real time, the user interface can run properly on the personal computer browser and smartphone responsively.